If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(B + -4) = 5B + 20 Reorder the terms: -5(-4 + B) = 5B + 20 (-4 * -5 + B * -5) = 5B + 20 (20 + -5B) = 5B + 20 Reorder the terms: 20 + -5B = 20 + 5B Add '-20' to each side of the equation. 20 + -20 + -5B = 20 + -20 + 5B Combine like terms: 20 + -20 = 0 0 + -5B = 20 + -20 + 5B -5B = 20 + -20 + 5B Combine like terms: 20 + -20 = 0 -5B = 0 + 5B -5B = 5B Solving -5B = 5B Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '-5B' to each side of the equation. -5B + -5B = 5B + -5B Combine like terms: -5B + -5B = -10B -10B = 5B + -5B Combine like terms: 5B + -5B = 0 -10B = 0 Divide each side by '-10'. B = 0.0 Simplifying B = 0.0
| -4.6+2.5=-3.8x+2.7 | | 14-8N=-2(5N-2) | | -5(7-3X)=19-3X | | -20-5P=5(4-5P) | | -6N-N=14 | | -8=-2P+6P | | K+3+6=11 | | 0=X-4-5X | | 2x+3+4x+1= | | -3N+3-6N=3 | | -4V-3V=-14 | | x(n-3)=4 | | 1+-.5= | | 1+.5x= | | 18x^2-27=35 | | 1.5(x+1)+3.5(x+1)=7.5 | | x^2+5x-10=-3x+10 | | 6x^2+2x-15=34-33x | | 28=4/7w | | 1/2w+3/4w | | 2-2=9x+2x | | 2e^4x-3=5 | | Ln(x)+ln(6)=2 | | 6=8s-3/4-20 | | -1+a/5=-4 | | 6x^2-2x+4=24 | | 8m+3=5m+18 | | x+(x*0.0975)=25 | | x^2-7x+4=-6 | | (-50)x(-4)= | | 5x^2+7x-16=32-27x | | (-8)x(-2)= |